Problematika Pembelajaran Bahasa Arab - Muliatno Muliatno (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
Teaching Arabic in Indonesia often faces linguistic and non-linguistic problems that must be resolved immediately. Linguistic problems, such as phonetics, morphology, and structure, while non-linguistic problems, include learning motivation, learning tools, teaching methods, study time, and learning environment. Language learning problems vary according to the age of the learner and the learning environment. This article reveals the problems of teaching Arabic in Indonesia.